Congregations as Consumers: Using Marketing Research to Study Church Attendance Motivations in The Diocese of Bandung Indonesia - Junianto, Pilifus (Journal Economics & Business Atmajaya Indonesia, 2018)
This study to applied techniques more commonly associated with the churchgoing orientation religious and church marketing mix. Data were collected using questionnaires filled out by 924 respondent who attendance in the Church of Diocese of Bandung. Its data processed by crosstabulation. Its tries to know whether there is the relationship between church marketing mix and churchgoing motivations with their attendance. The results indicated that there is connection between churchgoing motivations with their attendance and church marketing mix. Internal orientation of the respondent's religion has the highest influence among the orientations. Then in the church marketing mix, the greatest effect is the respondents are happy with the time schedule in Sunday Mass. It is in the access category